β-strand interactions at the domain interface critical for the stability of human lens γD-crystallin - Das, Payel (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Human age-onset cataracts are believed to be caused by the aggregation of partially unfolded or covalently damaged lens crystallin proteins; however, the exact molecular mechanism remains largely unknown. We have used microseconds of molecular dynamics simulations with explicit solvent to investigate the unfolding process of human lens γD-crystallin protein and its isolated domains. A partially unfolded folding intermediate of γD-crystallin is detected in simulations with its C-terminal domain (C-td) folded and N-terminal domain (N-td) unstructured, in excellent agreement with biochemical experiments. Our simulations strongly indicate that the stability and the folding mechanism of the N-td are regulated by the interdomain interactions, consistent with experimental observations. A hydrophobic folding core was identified within the C-td that is comprised of a and b strands from the Greek key motif 4, the one near the domain interface. Detailed analyses reveal a surprising non-native surface salt-bridge between Glu135 and Arg142 located at the end of the ab folded hairpin turn playing a critical role in stabilizing the folding core. On the other hand, an in silico single E135A substitution that disrupts this non-native Glu135-Arg142 salt-bridge causes significant destabilization to the folding core of the isolated C-td, which, in turn, induces unfolding of the N-td interface. These findings indicate that certain highly conserved charged residues, that is, Glu135 and Arg142, of γD-crystallin are crucial for stabilizing its hydrophobic domain interface in native conformation, and disruption of charges on the γD-crystallin surface might lead to unfolding and subsequent aggregation.